Design of Unipotential Electrostatic Lenses Operated Under zeroMagnification - جاسم, بلال خالد; احمد, احمد كمال; محمد, عبد الجبار (Al-Nahrain Journal of Science, 2010)
magnification and byusing inverse method in designing the electrostaticlens .The axial electrostatic potential is representedby suggesting a hyperbolic function. The paraxialray equation was solved to obtain the trajectory ofthe particles that satisfies the suggested potentialfunction .The optical properties such as thespherical and chromatic aberrations and focallength in the image side were determined .Theshape of the electrode of the electrostatic lens weredetermined by solving Laplace's equation and, theresults of this study showed a small values ofspherical and chromatic aberrations, which areconsidered as good criteria for good design.